Cancer Registration Needs Assessment at a Tertiary Medical Center in Kilimanjaro, Tanzania - Zullig, Leah L. (2013)
Cancer burden is increasing in Africa more any other continent, but population-based tracking of cancer incidence is incomplete. Cancer registries can improve understanding of cancer incidence. To assess organizational readiness to sustain registry development, we conducted a survey assessing change efficacy, resource availability, and change commitment at an academic hospital in Moshi, Tanzania. Fifty-two surveys were returned (80% response rate). There was strong reliability among change efficacy and commitment survey items with Cronbach’s alphas of 0.93 and 0.77, respectively. Clinicians, nurses, and administrators conveyed similar responses regarding change efficacy. Clinicians had similar responses for change commitment. Echoing many low- and middle-income countries, approximately one-third of respondents indicated there were no funds to maintain the registry and funds were not obtainable. For most resources respondents felt that resources were sufficient or attainable. Respondents were generally confident and committed to registry implementation. Lessons learned at KCMC may be more broadly relevant.